Efficacy and safety of the single-capsule combination of fluticasone/formoterol in patients with persistent asthma: a non-inferiority trial - Antilla,Marti (2014)
OBJECTIVE: Fluticasone and formoterol are effective in the treatment of asthma. When a corticosteroid alone fails to control asthma, combination therapy is the treatment of choice. The objective of this study was to compare the efficacy and safety of formulations containing budesonide/formoterol (BUD/FOR), fluticasone alone (FLU), and the single-capsule combination of fluticasone/formoterol (FLU/FOR) on lung function in patients with mild-to-moderate persistent asthma. METHODS: This was a randomized, multicenter, open phase III trial conducted in Brazil. The primary efficacy analysis was the assessment of non-inferiority between FLU/FOR and BUD/FOR combinations regarding FEV1 (in L) at the final visit. The secondary analyses were PEF, level of asthma control, serum cortisol levels, frequency of adverse events, adherence to treatment, and appropriate inhaler use. RESULTS: We randomized 243 patients to three groups: FLU/FOR (n = 79), BUD/FOR (n = 83), and FLU (n = 81). In terms of the mean FEV1 after 12 weeks of treatment, the difference between the FLU/FOR and BUD/FOR groups was 0.22 L (95% CI: −0.06 to 0.49), whereas the difference between the FLU/FOR and FLU groups was 0.26 L (95% CI: −0.002 to 0.52). Non-inferiority was demonstrated by the difference between the lower limits of the two 95% CIs (−0.06 vs. −0.002). The level of asthma control and PEF were significantly greater in the FLU/FOR and BUD/FOR groups than in the FLU group. There were no significant differences among the groups regarding patient adherence, patient inhaler use, or safety profile of the formulations. CONCLUSIONS: The single-capsule combination of FLU/FOR showed non-inferiority to the BUD/FOR and FLU formulations regarding efficacy and safety, making it a new treatment option for persistent asthma.